GTD Model Based Cubic Spline Interpolation Method for Wide-Band Frequency- and Angular- Sweep - Liu, Zhiwei; Chen, Rushan; Ding, Dazhi; Le, Luo (Applied Computational Electromagnetics Society Journal (ACES), 2022)
A hybrid frequency- and angularsweep interpolation method is proposed for the efficient analysis of the scattering over a broad frequency and angular band. This method hybridizes the cubic spline interpolation method and the GTD model. The cubic spline interpolation method is applied to interpolate the induced currents in the angular domain. The GTD model combined with the matrix pencil method is applied to parameterize the scattering centers over a wide frequency band. In order to efficiently compute electromagnetic scattering, the flexible general minimal residual (FGMRES) iterative solver is applied to compute the coefficients of Rao-Wilton- Glisson (RWG) basis functions. Therefore, a great deal of time can be saved for the calculation of frequency- and angular- sweep. Numerical results demonstrate that this hybrid method is efficient for wide-band RCS calculation with high accuracy.